Ao leitor... as batatas : um estudo sobre a recepção de Machado de Assis por alunos do ensino médio - Oliveira Júnior, Osvaldo Soares de (2010)
The main objective of the present work is to analyze the understanding of the works of the Brazilian classic writer Machado de Assis among secondary school students of the second grade (about 15 to 17 years old) in two schools in the city of Rio de Janeiro - one public and one private. The two centers were visited to analyze how those works are being read by students, which teaching methods were applied to present them and stimulate reading, and in how far the critical content of the books was explained to help the readers. During the period of my research, I got to know from the inside the mechanisms that drive education, and was able to describe teaching methods, as well as the encounter of students with the works. It was found out that the two establishments, despite profound social differences that separate them, have common difficulties. Those are: a lack of literature reading habits among a relevant part of the students, which is making the contact with the works of Machado de Assis harder; the lack of consolidation of reading skills that would otherwise facilitate the contact with the texts; and the difficulty among a significant part of the readers to go below the surface of the texts and reach deeper levels of meaning. Nevertheless, it was also noted that despite the difficulties, a communication between these readers and the unlimited potential of these works is possible